IMPLEMENTASI STRATEGI PEMASARAN USAHA BETA BOBA PERSPEKTIF BISNIS ISLAM - Tasyri Kamil; Arizal Hamizar; Andi I Marasabessy; Afdhal Yaman (PT. Hafasy Dwi Nawasena, 2024)
This research aims to determine the implementation of Beta Boba's business marketing strategy. And see how Beta Boba's business marketing strategy is implemented from an Islamic business perspective. The type of research used in this research is field research, namely research that focuses on a case intensively and in detail regarding the background of the current situation in question. This research uses a qualitative type with a descriptive approach method, namely describing in depth what is objectively according to the data collected. Based on the research results, the implementation of Beta Boba's business strategy has the potential to develop because the implementation of the strategy is very good and wide, such as business premises at the campus junction as well as social media even though there are many market competitors. The implementation of Beta Boba's business strategy has also implemented Islamic principles in running its business as stated in the interview results that the Beta Boba business owner has carried out polite behavior when receiving customers.